The concept of Bharatavarsha and other essays - Chattopadhyaya, Brajadulal (SUNY series in Hindu studies)
"This collection explores what may be called the idea of India in ancient times. Its undeclared objective is to identify key concepts which show early Indian civilization as distinct and differently oriented from other formations. The essays focus on ancient Indian texts within a variety of genres. They identify certain key terms--such as Janapada, Desa, Varna, Dharma, Bhava--in their empirical contexts to suggest that neither the ideas embedded in these terms nor the idea of Bharatvarsha as a whole are "given entities," but that they evolved historically. Professor Chattopadhyaya examines these texts to unveil historical processes. Without denying comparative history, he stresses that the internal dynamics of a society are best decoded via its own texts. His approach bears very effectively on understanding ongoing interactions between India's "Great Tradition" and "Little Traditions." As a whole, this book is critical of the notion of overarching Indian unity in the ancient period. It punctures the retrospective thrust of hegemonic nationalism as an ideology that has obscured the diverse textures of Indian civilization. Renowned for his scholarship on the ancient Indian past, Professor Chattopadhyaya's latest collection only consolidates his high international reputation"--